AB0408 Comparative effectiveness of abatacept versus tnfi in patients with rheumatoid arthritis who are ccp+ in the united states corrona registry. (15th June 2017) - Harrold, L; Litman, H; Connolly, S; Alemao, E; Price, K; Kelly, S; Rebello, S; Hua, W; Kremer, J
Abstract : Background: Anti-cyclic citrullinated peptide positivity (CCP+) is associated with a better response to abatacept (ABA) than anti-CCP negativity in patients (pts) with RA 1, 2 ; however, there are no head-to-head or comparative effectiveness research studies available evaluating responses to biologics in CCP+ pts in a real-world setting. Objectives: To compare the effectiveness of ABA vs a TNF inhibitor (TNFi) in pts with RA who are CCP+. Methods: We identified adult pts with RA from a large observational US cohort (1 Dec 2005–31 Aug 2016) who initiated ABA or a TNFi and who were CCP+ (≥20 U/mL) at or prior to initiation. Both groups had to have no prior exposure to other non-TNFi biologics or targeted synthetic DMARDs. TNFi initiators were excluded if they had prior use of ABA. Using propensity score matching (1:1) stratified by prior TNFi use (0, 1 and 2+), effectiveness at 6 months after initiation was evaluated. Mean change in CDAI over 6 months following initiation was the primary outcome, and secondary outcomes were: achievement of remission (CDAI ≤2.8), modified (m)ACR20, 50 and 70 responses and achievement of LDA/remission (CDAI ≤10) in those with moderate/high disease activity at initiation. A subset analysis was performed to consider separately pts who were biologic naïve and those who were biologic experienced at initiation. Results: The 330 pairs of propensity score-matched ABA and TNFi initiators had no substantial differences in baseline characteristics. Both treatment groups had similar mean change in CDAI at 6 months as well as achievement of LDA, remission and mACR20/50/70 responses (Table). Among the 97 matched biologic-naïve pairs, there was no significant difference in change in CDAI for ABA initiators vs TNFi initiators (p=0.19). However, in the 233 matched biologic-experienced pairs, those initiating ABA had a greater improvement in mean change in CDAI (p=0.033) and were more likely to achieve an mACR50 response (p=0.014). Conclusions: Pts with RA who were CCP+ and received either ABA or TNFi had a substantial improvement in clinical disease activity. In the overall propensity score-matched sample, similar outcomes were observed for both treatment groups. However, analysis of the biologic-experienced cohort found that ABA initiators had a greater improvement in disease activity than TNFi initiators. References: Sokolove J, et al. Ann Rheum Dis 2016;75:709–14. Harrold LR, et al. Ann Rheum Dis 2016;75(Suppl 2):505–6. Disclosure of Interest: L. Harrold Shareholder of: Corrona, LLC, Grant/research support from: Pfizer, Consultant for: Roche, Employee of: Corrona, LLC, H. Litman Employee of: Corrona, LLC, S. Connolly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, K. Price Employee of: Bristol-Myers Squibb, S. Kelly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Rebello Employee of: Corrona, LLC, W. Hua Employee of: Corrona, LLC, J. Kremer Shareholder of: Corrona, LLC, Grant/research support from: AbbVie, Genentech, Lilly, Novartis, Pfizer, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Genentech, GSK, Lilly, MedImmune, Pfizer, Sanofi, Employee of: Corrona, LLC